Colorectal Cancer in Inflammatory Bowel Disease - Nebbia, Martina; Yassin, Nuha A.; Spinelli, Antonino (Clinics in Colon and Rectal Surgery, 2020)
Patients with inflammatory bowel disease (IBD) are at an increased risk for developing colorectal cancer (CRC). However, the incidence has declined over the past 30 years, which is probably attributed to raise awareness, successful CRC surveillance programs and improved control of mucosal inflammation through chemoprevention. The risk factors for IBD-related CRC include more severe disease (as reflected by the extent of disease and the duration of poorly controlled disease), family history of CRC, pseudo polyps, primary sclerosing cholangitis, and male sex. The molecular pathogenesis of inflammatory epithelium might play a critical role in the development of CRC. IBD-related CRC is characterized by fewer rectal tumors, more synchronous and poorly differentiated tumors compared with sporadic cancers. There is no significant difference in sex distribution, stage at presentation, or survival. Surveillance is vital for the detection and subsequently management of dysplasia. Most guidelines recommend initiation of surveillance colonoscopy at 8 to 10 years after IBD diagnosis, followed by subsequent surveillance of 1 to 2 yearly intervals. Traditionally, surveillance colonoscopies with random colonic biopsies were used. However, recent data suggest that high definition and chromoendoscopy are better methods of surveillance by improving sensitivity to previously “invisible” flat dysplastic lesions. Management of dysplasia, timing of surveillance, chemoprevention, and the surgical approaches are all areas that stimulate various discussions. The aim of this review is to provide an up-to-date focus on CRC in IBD, from laboratory to bedside.
Keywords: colorectal cancer; Crohn's disease; ulcerative colitis; dysplasia; surveillance; surgery; IBD